Distribusi Kasus Leptospirosis di Kabupaten Demak Jawa Tengah - kuswati, Kuswati; Suhartono, Suhartono; Nurjazuli, Nurjazuli (Jurnal Kesehatan Lingkungan Indonesia, 2016)
Title: Distribution of Leptospiosis Incidence in Demak District, Central JavaBackground: Leptospirosis is zoonotic disease caused by Leptospira bacteria and transmitted to human through contact with animal urine into contaminated environment. Demak District is one of the endemic area in Central - Java. The number of cases is fluctuative  over the year 2011-2016 with the peak of 20 cases in 2011, and It decreased at low number in 2016. Many factors may contributed such as water puddle, rat, and behaviour. Nowdays,the information about the distribution and spreading of cases was lacking. The purpose of this study was to describe the leptospiroses incidence based on the epidemiological variable and  spatially in Demak District.Method: It was an observational research using cross sectional design. The subjects were 89 cases over the year 2011-2016. The variables studied consisted of epidemiological variabels (man, place, and time), physical and biological environment factors, and behaviour aspects. Interviews and observation were conducted as the data collection  techniques.The collected data would be analysed descriptively and spatially.Result: The results of this research showed that the lepstospirosis incidence was –suffered more by male (66%) compared to female. Most of them (67,4%) were farmers. The peak of leptospirosis incidence occured in 2011. The existence of water puddle around the house, and drainage functioning as the media where the rat died. There were rats in the house where the cases occured (98,7%). Most of the subjects (66,7%) stated that they did their activities everyday in bare foot. Spatial analysis showed that Mranggen and Karangawen sub district had high numbers of leptospirosis cases.Conclusion: Most of the leptispirosis cases were suffered more by male compared to female and the subjects worked as  farmers. Mranggen and Karangnawen were two districts  with  high incidence of leptospirosis relatively. These areas  held a history as flooding areas in previous time.